The Influence of ROE, Intelectual Capital, Leverage, ROA, Liquidity, Dividend Policy on Financial Performance in the Food and Beverage Sub Sector Manufacturing Companies on IDX For The 2018 – 2020 Period - Wulandari, Bayu; Adriana br Bukit , Vince Titania; Manik , Delma Oriza; Napitupulu, Christina H. Grace; Tambunan , Elprida (Devotion : Journal of Research and Community Service, 2022)
This study aims to examine whether ROE, intellectual capital, leverage, ROA, liquidity, dividend policy have an effect on financial performance. This research was conducted on food and beverage sub-sector manufacturing companies for the period 2018–2020 with a research population of 26 (twenty six) companies listed on the Indonesia Stock Exchange. The sampling technique used here is a saturated sampling technique, namely the technique of determining the sample and then obtaining a sample of 23 (twenty three) companies. The data used are the financial statements of each sample company published through www.Idx.co.id. The research method used is descriptive method and multiple linear regression analysis method. The dependent variable is dividend policy, while the independent variable is ROE, intellectual capital, leverage, ROA, liquidity, dividend policy. The results show that partially ROE, Intellectual Capital, Leverage, ROA, Liquidity and Dividend Policy have a significant effect on the financial performance of the food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange (IDX 2018-2020).